1997
DOI: 10.1080/00102209708935620
|View full text |Cite
|
Sign up to set email alerts
|

Extension of the Lean Operating Limit for Natural Gas Fueling of a Spark Ignited Engine Using Hydrogen Blending

Abstract: The performance, emissions and combustion characteristics of lean mixtures of natural gas and hydrogen were studied in a conventional spark ignited engine. Specifically. mixtures of natural gas blended with 5, 10 and 15 percent by volume hydrogen were considered. Engine performance parameters included power (BH P], thermal efficiency (BTE), specific fuel consumption (BSFC), coefficient of variation in mean effective pressure, cumulative energy release schedule, and emissions of CO, NO,r and hydrocarbons. Major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 11 publications
1
36
0
2
Order By: Relevance
“…Engine research showed that adding a small amount of hydrogen into natural gas can improve the combustion characteristics and reduce exhaust emissions [1 6] . Meanwhile, the lean burn limit can be extended by hydrogen addition and lead to further improvement of thermal efficiency and decrease of exhaust emissions [7,8] .…”
Section: Methane Hydrogen Premixed Laminar Flame Synchrotron Photomentioning
confidence: 99%
“…Engine research showed that adding a small amount of hydrogen into natural gas can improve the combustion characteristics and reduce exhaust emissions [1 6] . Meanwhile, the lean burn limit can be extended by hydrogen addition and lead to further improvement of thermal efficiency and decrease of exhaust emissions [7,8] .…”
Section: Methane Hydrogen Premixed Laminar Flame Synchrotron Photomentioning
confidence: 99%
“…Studies in the literature related to the use of hydrogen as both the primary fuel and a fuel additive have been directed toward the effects of small amounts of hydrogen addition on hydrocarbon flame stability and pollutant formation under fuel-lean conditions. For example, studies in spark ignition engines clearly show the benefits of hydrogen blended with natural gas on exhaust emissions (Larson and Wallace, 1997) and on extending the lean engine operating limits (Meyers and Kubesh, 1997;Bell and Gupta, 1997). Early results in large-scale gas turbine combustors also indicate advantages to hydrogen addition.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of engine efficiency and the reduction of emissions could be realized by adding a small amount of hydrogen to natural gas under lean mixture operation [9][10][11]. The lean-burn capability of natural gas could be improved by hydrogen addition leading to further improvement of engine thermal efficiency and reduction in emissions [12,13]. Moreover, hydrogen addition could increase the tolerance of large EGR while maintaining low cycle-by-cycle variations and reducing engine NO x by 80% [14].…”
Section: Introductionmentioning
confidence: 99%